Journalism and emotion - Jukes, Stephen (London : SAGE Publications Ltd, 2020)
'Indispensable.... for anyone who cares about journalism.' - Professor Karin Wahl-Jorgensen How can we understand the complex relationship between journalism and emotion? In a world of live-streamed terror, polarised political debates and fake news, emotion has become central to our understanding of contemporary journalism. Including interviews with leading journalists throughout, Journalism and Emotion critically explores the impact of this new affective media environment, not just on the practice of journalism, but also the lived experience of journalists themselves. Bringing together theory and practice, Stephen Jukes explores: The history of objectivity and emotion in journalism, from pre-internet to digital. The'emotionalisation' of culture in today's populist media landscape. The blurring of boundaries between journalism and social media content. The professional practices of journalists working with emotive material. The mental health risks to journalists covering traumatic stories. The impact on journalists handling graphic user-generated content. In today's interactive, interconnected and participatory media environment, there is more emotive content being produced and shared than ever before. Journalism and Emotion helps you make sense of this, explaining how emotion is mobilised to influence public opinion, and how journalists themselves work with and through emotional material.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Journalism -- Methodology